(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study set out to examine the relationship between consumer awareness and coverage of digital TV services in Uganda. The study utilised a correlational cross-sectional survey design to collect the data. Semi-structured survey tools and interview guides were used to collect data from a sample of TV owners. Data was analyzed using the narrative, descriptive, Pearson correlation and regression analyses. The study established that consumer awareness predicts Coverage of Digital TV Services. It is recommended that there is need for revision of the current policy objective 4 a) so that it can cater for new media like social media to promote consumer awareness. The means of disseminating consumer awareness need to be diversified. Government should compel all content providers to create space in their programming for consumer awareness.